Inferior and Superior Analysis of the Main Character of Cerkak “Sendhang ing Pangangene Barji” by Irul S. Budianto: Psychological Study of Alfred Adler - Febriyola, Sheila Marta; Clarenita, Ananda (Centre for Literary and Cultural Studies, 2023)
This research analyses the inferior and superior forms of the main characters in the story “Sendhang Ing Pangangene Barji”. This study used a descriptive qualitative method. This research uses Alfred Adler's psychology approach theory. The data in this research is in the form of text quotations that describe the feelings of inferiority and superiority of the main character in the story